Electroencephalography findings in patients presenting to the ED for evaluation of seizures(,,) - Kadambi, Pooja (Am J Emerg Med, 2014)
BACKGROUND: Status epilepticus is a life-threatening, time-sensitive emergency. Acquiring an electroencephalogram (EEG) in the emergency department (ED) could impact therapeutic and disposition decisions for patients with suspected status epilepticus. OBJECTIVES: The objective of this study is to estimate the proportion of EEGs diagnostic for seizures in patients presenting to an ED with a complaint of seizures. METHODS: This retrospective chart review included adults presenting to the ED of an urban, academic, tertiary care hospital with suspected seizures or status epilepticus, who received an EEG within 24 hours of hospital admission. Data abstraction was performed by a single, trained, nonblinded abstractor. Seizures were defined as an epileptologist's diagnosis of either seizures or status epilepticus on EEG. The proportion of patients with seizures is given with confidence interval(95) (CI(95)). RESULTS: Of 120 included patients, 67 (56%) had a history of epilepsy. Mean age was 52 years (SD, 16), 58% were White, and 61% were male. Within 24 hours, 3% had an EEG diagnostic for seizures. Electroencephalogram was obtained in the ED in 32 (27%) of 120 (CI(95), 19%-35%), and 2 (6%) of 32 (CI(95), 1%-19%) had seizures. Electroencephalogram was performed inpatient for 88 (73%) of 120 (CI(95), 65%-81%), and 2 (2%) of 88 (CI(95), 0.5%-7.1%) had seizures. CONCLUSION: Only 3% of ED patients with suspected seizures or status epilepticus had EEG confirmation of seizures within 24 hours. Early EEG acquisition in the ED may identify a group of patients amenable to ED observation and subsequent discharge from the hospital.